2006
DOI: 10.1083/jcb1726oia14
|View full text |Cite
|
Sign up to set email alerts
|

In vivo role of ER-associated peptidase activity in tailoring peptides for presentation by MHC class Ia and class Ib molecules

Abstract: Endoplasmic reticulum (ER)-associated aminopeptidase (ERAP)1 has been implicated in the fi nal proteolytic processing of peptides presented by major histocompatibility complex (MHC) class I molecules. To evaluate the in vivo role of ERAP1, we have generated ERAP1-defi cient mice. Cell surface expression of the class Ia molecules H-2K b and H-2D b and of the class Ib molecule Qa-2 was signifi cantly reduced in these animals. Although cells from mutant animals exhibited reduced capacity to present several self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 17 publications
2
40
2
Order By: Relevance
“…The increase in GSW11 generation occurred despite an overall decrease in MHC I levels; MHC I downregulation is typically observed in ERAAP-knockout cells (Fig. 1D) (11)(12)(13)(14). This confirmed that the generation of GSW11 is ERAAP sensitive.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The increase in GSW11 generation occurred despite an overall decrease in MHC I levels; MHC I downregulation is typically observed in ERAAP-knockout cells (Fig. 1D) (11)(12)(13)(14). This confirmed that the generation of GSW11 is ERAAP sensitive.…”
Section: Resultssupporting
confidence: 68%
“…In humans, two aminopeptidases perform this function, ERAP1 and ERAP2 (7)(8)(9); in mice, only one aminopeptidase exists, ERAAP (10). ERAAP is critical for the generation of many antigenic epitopes in vivo and can influence the generation of the antigenic peptide repertoire (11)(12)(13)(14). ERAAP can also destroy antigenic epitopes by trimming them to lengths too small for MHC binding, thus its characterization as an antigenic peptide editor (12).…”
mentioning
confidence: 99%
“…ERAP-1-deficient mice had significantly less expression of HLA class I molecules on the cell surface and were less able to present self-and foreign antigens. Heterozygous ERAP-1 +/− mice showed an intermediate phenotype that suggest polymorphisms that affect ERAP-1 function could affect antigen presentation (17). ERAP-1 has recently been shown to be associated with anklyosing spondylitis, a condition strongly linked to another HLA class I molecule: HLA-B*27 (18).…”
Section: Functional Role Of Hla-b*51 In Bdmentioning
confidence: 99%
“…The latter feature refers to the low ERAP1-trimming activity toward most peptides shorter than eight residues (12,16). Absence of ERAP activity has been shown to drastically change the profile of MHC class I-associated peptides (17) and/or alter Ag presentation in vitro and in vivo in numerous experimental systems (18)(19)(20). ERAP2 has been proposed to have an accessory role in ER peptide trimming, because of its complementary N-terminal specificity (12).…”
Section: P Rocessing Of Ags For Presentation By Mhc Proteins Involvesmentioning
confidence: 99%